How to make Gari - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
Garri (also known as gari, garry, tapioca, or garium sulphate, a colloquial term for the crop especially used in southwest Nigeria) is a popular West African food made from cassava tubers. The spelling "garri" is mainly used in Nigeria, Cameroon and Ghana. This video tutorial showcase the step by step of making this popular west African food.